Labour, employment and economic growth in India - Ramaswamy, K. V. (New York : Cambridge University Press, 2015)
"Discusses some key aspects in the interrelated areas of economic development, employment and structural change"--
Economic growth and employment -- Introduction and review of issues / 1.K.V.Ramaswamy -- India's labour market during the 2000s / Jayan Jose Thomas -- Services-led growth and employment in India / Ajit Ghose -- Growth,structural change and poverty reduction : evidence from India / Rana Hasan, Sneha Lamba and Abhijit Sengupta -- Age structure transition, population ageing and economic growth : new evidence from India / M.R.Narayana -- Labour intensity in Indian manufacturing : measurement, patterns and determinants / Deb Kusum Das,Kunal Sen and Pilu Chandra Das -- Gender discrimination in manufacturing employment in India, 1999-2009 / B.N.Goldar and Suresh Aggarwal -- Employment and labour law -- From rigidity to flexibility : changes in the Indian labour market / Bibhas Saha -- Employment protection legislation and threshold effects / K.V.Ramaswamy -- Who is a worker? : searching the theory of the firm for answers / Jaivir Singh -- Labour jurisprudence of the supreme court : recent trends / Ramapriya Gopalakrishnan -- Index.
Includes bibliographical references and index.
Keywords: Labor supply -- India; Labor market -- India; Economic development -- India